Answer:
[tex]\mathrm{The\:solutions\:to\:the\:quadratic\:equation\:are:}[/tex]
[tex]x=\frac{1}{8},\:x=1[/tex]
Step-by-step explanation:
Given the equation
[tex]8x^2-9x=-1\:\:[/tex]
Add 1 to both sides
[tex]8x^2-9x+1=-1+1[/tex]
[tex]8x^2-9x+1=0[/tex]
as
[tex]\left(8x-1\right)\left(x-1\right)=8x^2-9x+1[/tex]
so the equation becomes
[tex]\left(8x-1\right)\left(x-1\right)=0[/tex]
Using the zero factor principle:
[tex]\:If}\:ab=0\:\mathrm{then}\:a=0\:\mathrm{or}\:b=0\:\left(\mathrm{or\:both}\:a=0\:\mathrm{and}\:b=0\right)[/tex]
so
[tex]8x-1=0\quad \mathrm{or}\quad \:x-1=0[/tex]
solving
[tex]8x-1=0[/tex]
[tex]8x=1[/tex]
[tex]\frac{8x}{8}=\frac{1}{8}[/tex]
[tex]x=\frac{1}{8}[/tex]
also solving
[tex]x-1=0[/tex]
[tex]x=1[/tex]
[tex]\mathrm{The\:solutions\:to\:the\:quadratic\:equation\:are:}[/tex]
[tex]x=\frac{1}{8},\:x=1[/tex]